Player Walks Off, Delays Pan Prelims:…Claims Band Refusing to Pay - Francis, Innis (Saturday Express)
Patrons attending the preliminary round of the Panorama competition for conventional bands in the small and medium category waited for half an hour before the band Antilleans All Stars began its performance. The delay arose when Antillean All Star players were already on stage and the band's drummer, Vincent Edwards, walked off with his drum in hand claiming that he was owed money.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Panorama (Musical festival); Steel band music -- Trinidad and Tobago